STEM-CTL: An Initiative to Promote Elementary School Students’ Critical Thinking Skills - Maryani, Ika; Yuliana, Ica; Islahuddin (The Indonesian Institute of Science and Technology Research, 2024)
The present study employed a quasi-experimental, one-group pretest-posttest design to examine the effectiveness of the STEM-CTL model in promoting critical thinking among elementary school students. The study sample consisted of 34 students from 4th grade at an elementary school. They were selected using the non-probability sampling technique. The independent research variable was STEM-CTL, while the dependent variables consisted of critical thinking aspects, including the ability to formulate a problem, the ability to give arguments, the ability to make deductions and inductions, and the ability to draw inferences. Data on participants’ critical thinking were collected using a test and analyzed using descriptive and inferential statistics (paired sample t-test). The analysis results revealed a significant effect of STEM-CTL on participants’ critical thinking skills (at a significance level of 0.000 > 0.05). Hence, H0 was rejected, and Ha was accepted. The N-gain score was medium (0.63), indicating that STEM-CTL effectively promoted critical thinking skills among elementary school students.